Transitivity Analysis of Luh Ayu Manik's Narrative Text: Unveiling Character and Action Dynamics - Suari, A. A. Pt.; Artawa, I Ketut; Sudewa, I Ketut; Aryawibawa, Nyoman (Randwick International of Social Science Journal, 2024)
This study investigates the depiction of characters in the narrative text Luh Ayu Manik – Tresna ring Alas through the application of transitivity processes within the framework of Systemic Functional Linguistics. Utilizing a qualitative approach, the research analyzes various linguistic processes—including Material, Mental, Relational, Behavioral, and Verbal—to examine how these processes portray the main character and supporting characters. The findings reveal that Luh Ayu Manik is depicted as proactive and courageous through Material processes, introspective and empathetic through Mental processes, and responsible and caring through Relational processes. Her perseverance is emphasized through Behavioral processes, while her leadership is demonstrated through Verbal processes. Additionally, the analysis uncovers the complex roles of supporting characters such as Made Anjasmara and Ketut Suprabawa Kabinawa, who are portrayed as brave and strategic in their actions. Meanwhile, the antagonistic characters, the thieves, are depicted through destructive actions and complex emotional responses, highlighting their role as significant threats to the environment. This study contributes to a deeper understanding of character development and narrative dynamics, demonstrating the effectiveness of transitivity analysis in uncovering detailed character attributes and interactions.